Developing Independent Media as An Institution of Accountable Governance : A How-To Guide - Kalathil, Shanthi (World Bank, 2012)
The World Bank's Communication for Governance and Accountability Program (CommGAP) has spent several years exploring the linkages between the media and governance reform. The first stage of this process produced public sentinel: news media and governance reform, an edited volume that explored key issues surrounding the role of the media in democratic governance and the policy interventions that might enable this role. This how-to guide represents the second stage of that process: turning theoretical and policy conclusions into a practical guide for those seeking to enhance good governance by empowering the media. An early needs assessment revealed limited understanding of media development and the role it can play in foster accountable governance. This toolkit accordingly provides the why, how, when, and what of supporting the development of independent, pluralistic and sustainable media.